Optimalisasi Gerakan Sadar Wisata melalui Produksi Video Promosi Desa Wisata - Diyah Indiyati; Hartin Nur Khusnia; Siti Chotijah (Jurnal Pengabdian Pada Masyarakat, 2020)
OPTIMIZATION OF TOURISM CONSCIOUS MOVEMENT THROUGH VIDEO PRODUCTION OF TOURISM VILLAGE PROMOTION. West Nusa Tenggara has set the tourism sector become one of the backbone of regional development. NTB Province government also sets the growth target of the tourism industry to increase annually. For 2018, NTB has set a target of tourist arrivals reaching up to 4 million tourists. Various improvements were made, especially in the fields of infrastructure and accessibility in this region, as well as tourism promotion programs. The regional government certainly has allocated a budget for tourism promotions, but tourism promotions will not only be effective if it is carried out by the government alone. The community needs to participate in this tourism promotion effort. This Community Service Program offers tourism promotion efforts with participatory concepts carried out by youth who are members of the Pemuda Rinjani Mandiri (Prima) tourism awareness group. The hope is that promotional efforts can be carried out in accordance with the potential and values ​​of local wisdom that live in the community. One of the promotional efforts that will be carried out is through the production of promotional videos for Lantan Tourism Village which will be the product of this community empowerment program.